Two-day hangover - Sullivan, Derek ([Toronto] : D. Sullivan, 2008)
A bookwork by Sullivan, left incomplete and open for continual revisions and additions. This working version is comprised of images taken by the artist during a brief tour of Paris. Cityscapes, museum antiquities and displays, snapshot self-portraits and other curiosities fill the pages not left blank. From a group of books published by Sullivan, for his White Column's Bulletin Board project, using print on demand technology. The technology allows for the content of the titles to be under continual revision, creating an unlimited edition publication that is in perpetual development.
boek